A positive readout single transcript reporter for site-specific mRNA cleavage - Kandul, Nikolay; Guo, Ming; Hay, Bruce A. (PeerJ, 2017)
Cleavage of mRNA molecules causes their rapid degradation, thereby playing an important role in regulation of gene expression and host genome defense from viruses and transposons in bacterial and eukaryotic cells. Current negative-readout, and repressor-based positive-readout reporters of mRNA degradation have limitations. Here we report the development of a single transcript that acts as a positive reporter of mRNA cleavage. We show that placement of bacterial CopT and CopA hairpins into the 5′ UTR and 3′ UTR of an mRNA results in inhibition of translation of the intervening coding sequence in Drosophila. An internal poly(A) tract inserted downstream of the coding sequence stabilizes transcripts cut within the 3′ UTR. When these components are combined in a transcript in which targets sites for RNA cleavage are placed between the poly(A) tract and CopA, cleavage results in translational activation, providing a single transcript-based method of sensing mRNA cleavage with a positive readout.
Keywords: Poly(A); Translation; Positive-readout; RNA hairpins; CopT-CopA; Auto-repression; Reporter